DOBROWOLNE PODDANIE SIĘ ODPOWIEDZIALNOŚCI W PRAWIE KARNYM SKARBOWYM. UWAGI ‘DE LEGE FERENDA’ - Czichy, Krzysztof (Zeszyty Prawnicze, 2017)
Voluntary Acceptance of Liability in Fiscal Criminal Law. Remarks on Relevant Legislation Summary Voluntary acceptance of liability is one of the most commonly used institutions for the reduction of fiscal criminal liability. The purpose of this study is to answer question whether the current regulations are working efficiently, or whether modification is needed.